The Perennial Problems of Forest Fires in North America and Australia: Lessons for Policymaking and Design - Manzvera, Notion; Hickonicko, Beatrice; Ndemo, Nyasha (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2025)
The article is based on a study that discusses the perennial problems of forest fires in North America and Australia, presenting lessons for policy-making and design. Wildfires present problems in the North American (the United States and Canada) and Australian regions as they continue to cause huge losses in ecosystems, vegetation and loss of human life. The problem in the study is that the bushfires continue to claim human life and indigenous ecosystems causing the invasion of the landscape by flammable invasive plants that worsen the bushfires leading to the increase of climate change. The study uses a qualitative approach with a bias towards a case study research design. The research employs secondary information as the data collection method. Thematic analysis is used as the data analysis method. The study findings reveal that the impacts of forest fires are on the ecosystems and the hydrological systems that are affected, worsening climate change. The study concludes that the responses to forest fires have shown a lack of preparedness and eagerness to erase the industrial cities in favour of smart cities in the rebuilding. The study recommends the systematic technological integration of machines in risk disaster management.